The Impact of Digital Learning on Media on Thematic Education - Safitri, Elza; Purnamasari, Lora (RADINKA JAYA UTAMA PUBLISHER, 2023)
Digital technology is used in education to support learning activities. Teaching using learning tools. This research was conducted to identify related impacts caused by the use of digital learning media on thematic learning for elementary school students. Research methods SLR (Systematic Literature Review) articles were used. In this research, seven articles in national journals met the criteria determined by researchers from 2015 to 2023. Watch learning resources. digital that can be used by junior high school students for thematic teaching Supported applications such as Google Classroom, WhatsApp group, and Canva with animations, learning videos, PowerPoint, and digital comics. According to literature research conducted, media use Students can improve their learning outcomes by using continuously updated digital technology. This is proven by students' ability to acquire and understand the material., reducing student boredom and increasing student focus to understand this learning, which can be adapted to both the needs and transformations of the modern age.